Geospatial Analysis of Informal Settlement Development in Cape Town - Fisher, Toufeeq (School of Architecture, Planning and Geomatics, 2024)
A significant factor in the growth of cities is the development of informal settlements. Informal settlements are associated with negative socio-economic factors such as unemployment and a lack of secure land tenure. Over one billion people live in such settlements all around the world, and consequently, informal settlers are exposed to the effects of negative socio- economic factors. This research focuses on understanding how informal settlements develop within the City of Cape Town using spatial metrics. By understanding the development, informed steps can be taken to improve the quality-of-life informal dwellers are exposed to. The development of three informal settlements was monitored: Imizamo Yethu, Langa and Siqalo. Initially, machine learning techniques were used to determine the current development, complexity, and compactness of informal housing within settlements. High-resolution imagery was used to classify shacks in the targeted informal settlements. An accuracy assessment was conducted to validate any subsequent analysis that was completed from classified imagery. The overall accuracies ranged between 88-96%. Thereafter, change detection analysis would be used to understand how each informal settlement developed and would be compared to each other. Using the combination of change detection, linear regression, and ordinary least squares analysis across the selected informal settlements, results from this study showed that the major development characteristic was the densification of shacks. This densification followed along major formal and external transport routes, as well as informal and internal transport networks. Densification was also heavily driven by open space. There were also individual and unique internal development dynamics in each informal settlement. These were driven by slopes, employment opportunities, and neighbouring income areas. The most statistically significant factor that influenced development across all the informal settlements was open space. This was determined through ordinary least squares.